Towards Modern Collaborative Knowledge Sharing Systems - Lipiński, Piotr; Świrski, Konrad (Studies in Computational Intelligence, 2012)
The development of new technologies still accelerates. As a result the requirement of easy access to high quality information is essential in modern scientific society. We believe that new cloud-based online system will replace the old system of books and magazines in the future. This is mainly because contemporary system of journal and conference publications appears to be outdated, especially in such domains as computer science, because process of publishing of an article takes too much time. In this book a new approach of sharing knowledge is proposed. The main idea behind this new approach is to take advantage of collaboration techniques used in industry to share the knowledge and build teams which work on the same subject at different locations. This will allow to accelerate the exchange of information between scientists and allow to build global teams of researchers who deal with the same scientific subjects. Furthermore, an easy access to structured knowledge will facilitate cross domain cooperation. This book describes the concept of a cross-domain platform which can be used for scientific cooperation. It also familiarizes readers with new concepts and technologies which are used in the platform and introduces the first projects which are developed using this technology. It is expected to be of special interest to researchers and professionals in computer science and mechanics.